A Study on Nutrient Adequacy in Pre-school Children of Women Migrant Laborers in Ludhiana City. (1st April 2016) - Arora, Prapti; Kaur, Harpreet; Bains, Kiran
Abstract: One hundred and twenty children in the age group of 3-6 years of women migrant laborers that are domestic and construction laborers were selected from Ludhiana city by random sampling. The information regarding the quantities of foods consumed was collected from the mothers of the subjects by a 24-hour recall method. The daily mean intake of cereals and pulses was ninety-five and ninety-one percent of the suggested dietary intake, respectively. The daily mean intake of milk and milk products was thirteen percent and that of fruits and vegetables varies from eighteen to twenty-nine percent of the suggested amount indicating poor intake. The nutrient intake in all selected preschool children was found to be inadequate except protein intake and vitamin B12 intake. The study concluded that the food and nutrient intake of children of both domestic and construction women laborers was inadequate. The study recommends that the mothers should be educated about appropriate feeding practices and selection of right foods for their children in order to achieve optimum health for them in their limited resources.